Lembrando Lísias - Concone, Maria Helena Villas Bôas (PLURA, Revista de Estudos de Religião / PLURA, Journal for the Study of Religion, 2017)
<span style="font-size: 13.0pt; mso-bidi-font-size: 12.0pt; font-family: ";Bookman Old Style";,";serif";; mso-fareast-font-family: SimSun; mso-bidi-font-family: Arial; mso-font-kerning: 13.0pt; mso-ansi-language: PT-BR; mso-fareast-language: ZH-CN; mso-bidi-language: HI;">Lembrando<span style="font-size: 13.0pt; mso-bidi-font-size: 12.0pt; font-family: ";Bookman Old Style";,";serif";; mso-fareast-font-family: ";Times New Roman";; mso-bidi-font-family: ";Times New Roman";; mso-font-kerning: 13.0pt; mso-ansi-language: PT-BR; mso-fareast-language: ZH-CN; mso-bidi-language: HI;"> <span style="font-size: 13.0pt; mso-bidi-font-size: 12.0pt; font-family: ";Bookman Old Style";,";serif";; mso-fareast-font-family: SimSun; mso-bidi-font-family: Arial; mso-font-kerning: 13.0pt; mso-ansi-language: PT-BR; mso-fareast-language: ZH-CN; mso-bidi-language: HI;">Lísias